Correlation between gut pathogens and fecal calprotectin levels in young children with acute diarrhea - Yanever Angela Lam; Sarah M. Warouw; Audrey M.I. Wahani; Jeanette I.C. Manoppo; Praevilia Margareth Salendu (Indonesian Pediatric Society, 2014)
Background In cases of acute diarrhea, it is difficult to distinguishbetween bact erial and non-bacterial causes . Increased fecalcalprotectin (f-CP) level is a marker of neutrophil migration in theintestinal lumen and is associated with intes tinal inflammation.Previous studies reported an increase in f-CP levels in childrenwith acute diarrhea, which is caused by bacteria, but only fewhave studied the relationship between intestinal pathogens withf-CP levels in acute diarrhea.Objective To assess for a correlation between gut pathogens andfecal calprotectin levels in children with acute diarrhea.Methods We conducted a cross-sectional study between Julyto November 2012 on children aged 1-5 ye ars with acutediarrhea, and underwent routine blood tests, stool microscopy,f-CP tests, and stool cultures. We used a simple linear regressionand correlation analysis with a significance level of P< 0.05.Results Forty-two children enrolled in this study. The mean age ofsubjects was 2.27 (SD 134) years. Theirmeanf-CP level was 93.88(SD 14.68) Î¼g/g. On microscopic stool examination, 26 patients( 61.9%) had positive leukocytes, 1 had Ancy lo stoma duodenale, 1had Ascaris lumbricoides, and 2 had Blastocystis hominis. Positivestool cultures were found in 14 children (33.3%) with acutediarrhea. There was a significant positive correlation between gutpathogens and f-CP levels (r=0.605; P< 0.0001).Conclusion In young children with acute diarrhea, the averagef-CP levels are higher in those with positive intestinal pathogens.